Crystal structure of poly[(μ2-nitrato-κ3 O,O′:O′′)(μ2-1-[(2-propyl-1H-benzimidazole-1-yl)methyl]-1H-benzotriazole-k2 N:N′)silver(I)], C17H17AgN6O3 - Cheng Ling-He; Cao Meng-meng; Zhang Hai-Long; Wang Xiao; Liu Yang-Yu (Zeitschrift für Kristallographie - New Crystal Structures)
C17H17AgN6O3, monoclinic, P21/c, a = 9.7281(3) Å, b = 18.8761(6) Å, c = 9.6289(3) Å, β = 99.548(3)∘, Z = 4, V = 1743.65(10) Å3, R gt(F) = 0.0465, wR ref(F 2) = 0.1193, T = 293 K.